(untitled) (Indian Journal of Public Health Research & Development, 2021)
Background: Yoga is a form of alternative medicine, which aims for an overall physical, mental, and spiritual health. Several benefits of yoga in terms of disease prevention have been well documented in literature. However, there is a lack in the studies relating to its prevalence, especially in the Indian scenario. Here we aimed to decipher the prevalence of yoga practice in the Kolhapur population. Method: A survey was conducted on 5003 residents of Kolhapur. The survey was designed to evaluate the knowledge and practice of yoga in the respondents. Socio-demographic variables were presented by MSExcel. Logistic regression was performed by R-studio 1.2.5001. Results: Most of the yoga users were between 40-49 years. The primary occupation of most of them was service. Men were more likely to practice yoga, as compared to females (OR-0.29, P<0.05). Also, older (OR-1., P<0.5) and retired people (OR-1.8, P<0.05) were more like to practice yoga. Yoga was also shown to be mostly practiced among people of higher economic status as opposed to people with low economic status. Conclusion: This is the first study on the prevalence of yoga practice in Kolhapur population. Results depict that a considerable number of people knew about yoga, but only a few of them practiced it. Additional studies are thus required for a better deduction of yoga prevalence.